Spiritual Rituals in Creating the Morality of Indonesian Students in Sakarya Turkey - Eliza Alfareza (Jurnal Studi Agama, 2022)
This research examines the spiritual rituals pioneered by the Indonesian Student Association (PPI) in the city of Sakarya, Turkey. This study aims to determine the impact and role of spiritual rituals on the condition of the morality of Indonesian students in the city of Sakarya, Turkey. This research is categorized as field research. Data collection was carried out using observation and interview techniques, while data analysis using descriptive-qualitative techniques. This study found that spiritual rituals initiated by the Indonesian Student Association (PPI) can create intimacy between Indonesian students who are in Sakarya Turkey. Spiritual rituals are performed once every two weeks. This activity begins with reading the Qur'an, prayers, and scientific discussions, and closes with dinner together. This activity was carried out in turns at the residence of Indonesian students in Sakarya. In addition, it was also found that spiritual rituals had a positive impact on the morality of Indonesian students at Sakarya such as; the absence of sects between students, the disappearance of gaps between social groups, and the creation of a space for discussion and friendship between students.